2012
DOI: 10.1123/jpah.9.4.525
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Efficacy of a Brief Motivational Intervention Designed to Increase Physical Activity Among College Students

Abstract: Background:Research has shown that many college students do not meet recommended national guidelines for physical activity. The objective of this pilot study was to examine the short-term efficacy of a brief motivational intervention (BMI) designed to increase physical activity.Methods:Participants were 70 college students who reported low physical activity (83% women, 60% African American). Participants were randomly assigned to either the BMI condition or to an education-only (EO) condition. They completed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…Notably, the increase in health-related behaviors seen in physiotherapy students (study group) and in other students (control group) was consistent with the trend observed in the general Israeli population reflected in surveys conducted by the Israeli Ministry of Health [21–24], which indicated an improvement in PA commitments of the general Israeli population in comparison to previous surveys. The results of our study supported results from previous studies [5,19–21] regarding the importance of an intervention to include practice as well as theoretical knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, the increase in health-related behaviors seen in physiotherapy students (study group) and in other students (control group) was consistent with the trend observed in the general Israeli population reflected in surveys conducted by the Israeli Ministry of Health [21–24], which indicated an improvement in PA commitments of the general Israeli population in comparison to previous surveys. The results of our study supported results from previous studies [5,19–21] regarding the importance of an intervention to include practice as well as theoretical knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…A randomized trial in 2012 examined the short-term efficacy of a brief motivational intervention (BMI) designed to increase PA [5]. Seventeen college participants were randomly assigned to either the BMI or to an education-only (EO) intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our results suggest that the same self-regulation skills should be addressed when aiming to decrease sedentary behaviour during this transition period. A randomised trial in college students showed that a 30-minute single session of one-on-one motivational interviewing (including discussing perceived benefits and barriers, personalised feedback, goal setting and strategies for increasing physical activity levels) increased moderate and vigorous physical activity levels after one month [42]. Although no long-term effects were evaluated, a single session intervention as such may be more appealing to college students and easier to implement on college campuses in comparison to more intensive models [42].…”
Section: Discussionmentioning
confidence: 99%